Phytochemical Profile of Urtica dioica L. by Gas Chromatography-Mass Spectrometry GC-MS and Antioxidant Activity - Alanbari, Aseel K.; Alddin, Ragha Safaa; Mohammed, Wurood Khald (Universitas Muhammadiyah Sidoarjo, 2025)
Leaves are rich in many phytochemical compounds, all bioactive compounds formed normally during plants metabolism as secondary products. The phytochemical compounds screened by gas chromatography-mass spectrometry (GC-MS) method. Twenty nine bioactive phytochemical compounds were identified in the . The GC-MS analysis of U. dioica revealed the identification of phytochemical compounds is based on the peak area, retention time ., as well as the antioxidant activities of the leaves were determine. . the first compound was benzene that presence at 5.339 min with peak area 1.18, while the 9-Octadecenamide was the last compound shown at 68.304 min with 2.18 peak area. Including organic compounds, fatty acids and phenols. A DPPH radical scavenging e results showed U. dioica extract at 600 concentrations high than ascorbic acid was93.76 µg/ml while aceorbic acid was 91.14 µg/ml. this finding indicate that U. dioica have high antioxidant ability. . This manuscript to cover the chemical composition of methanolic extract of U. dioica leaves ( stinging nettile) that growing naturally in Iraq, as a chemical study and provide details of pharmacological propos